Fighting EOKA - French, David.
1 online resource (347 pages)
Keywords: The first full account of the operations of the British security forces on Cyprus in the second half of the 1950s, showing how these forces were trying to defeat the Greek Cypriot paramilitary organisation, EOKA, which was fighting to bring about union between Cyprus and Greece.